Google Translate in Vocabulary Learning: The Positive Impact and The Drawbacks - Hutagalung, Genta; Ningsih, Wirda; Rohliah, Leni; Lestari, Pratiwi (Foremost Journal, 2024)
This article aims to 1) explicate the positive impact of using Google Translate in vocabulary learning and 2) to explicate the drawback of using Google Translate in vocabulary learning. The method used in this writing this article is Systematic Literature Review (SRs). To analyse the data, the writer used content analysis technique. The result of the study shows that Google Translate was found to enhance student engagement and self-awareness in their learning process. Google Translate also helped them master vocabulary because it is easy to use and accessible. It also assisted students to improve their vocabulary with words with similar meaning. Moreover, Google Translate could be used for spelling check. On the other hand, Google Translate also have drawbacks such as causing dependency for students. Students were too reliant on it causing them to give less attention to the vocabulary’s deeper meaning. It is also not beneficial for students who want to learn figurative language because it cannot process figurative language well which may lead to the inaccuracy of the translation. Therefore, it is suggested that to maximize the use of Google Translate in vocabulary learning, students need to be assisted by their teachers.